Peristiwa Isra' Mi'raj Nabi Muhammad SAW dan Pembelajarannya - Yuyun Yunita (Jurnal Dewantara, 2021)
Israj Mi'raj is the event of the Prophet's journey from the Haram Mosque to the Aqsh Mosque, then the Prophet was brought up to Sidaratul vomitingara by the angel Gabriel by riding the Buraq. On this occasion Muslims were ordered to perform the five daily prayers. The person who first confirmed this incident was Abu Bakr for his bravery he earned the title as-Siddiq "brave". This incident has been described in Q.S Al-Isra '1 and in Q.S An-Najm verses 13-18 where it is explained that the Messenger of Allah met Allah SWT directly and without any obstacles. The Messenger of Allah also knows the signs of Allah's greatness, the recompense for those who like to disobey Allah's commands, and the recompense for those who carry out Allah's commands. In this event we can also take lessons that we can apply in everyday life.